2017
DOI: 10.1002/prot.25325
|View full text |Cite
|
Sign up to set email alerts
|

Structural review of PPARγ in complex with ligands: Cartesian- and dihedral angle principal component analyses of X-ray crystallographic data

Abstract: Two decades of research into the ligand-dependent modulation of the activity of the peroxisome proliferator-activated receptor γ (PPARγ) have demonstrated the heterogeneous modes of action of PPARγ ligands, in terms of their interaction surfaces in the ligand-binding pocket, binding stoichiometry and ability to interact with functionally important parts of the receptor, through both direct and allosteric mechanisms. These findings signal the complex mechanistic bases of the distinct biological effects of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…We also started apo aMD simulations with helix 12 in an alternate crystal contact induced conformation 45 , which we refer to as the inactive structure. This conformation is very different from the canonical active conformation; the helical axis of this inactive helix 12 conformation is nearly orthogonal to the active axis (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also started apo aMD simulations with helix 12 in an alternate crystal contact induced conformation 45 , which we refer to as the inactive structure. This conformation is very different from the canonical active conformation; the helical axis of this inactive helix 12 conformation is nearly orthogonal to the active axis (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structures showed that the conformation of helix 12 is different when bound to a corepressor (SMRT) (H. E. Xu et al, 2002) versus a coactivator (e.g., SRC1) (Nolte et al, 1998). Surprisingly, crystal structures of PPARγ bound to full agonists, antagonists, and inverse agonists are remarkably similar (Kaupang, Laitinen, Poso, & Hansen, 2017). In contrast, solution state methods, including protein and fluorine NMR, simulation, hydrogen-deuterium exchange mass spectrometry (HDX-MS), and fluorescence anisotropy demonstrate that ligands have dramatic and varied effects on the structural state of PPAR (J.…”
Section: Advances In Ppar Structure-functionmentioning
confidence: 99%